Advancing Lithium Niobate Based Thin Film Devices for 5G Front-Ends - Yansong Yang; Ruochen Lu; Kourani, Ali; Songbin Gong (2019 IEEE MTT-S International Microwave Symposium (IMS), 2019)
A brief review of the motivations and development effort for LN thin film devices is offered before recent advances on LN thin film devices are reported. LN devices for a sub-6 GHz band and X-band have designed and fabricated. As a result of the design and implementation effort, the most advanced LN resonator is reported at 1.7 GHz with a k t 2 of 14%, a high Q of 3112, a FoM of 435, and a spurious-free response, greatly surpassing the state of art at this frequency range. An acoustic prototype filter at 10 GHz is also demonstrated with an insertion loss of 3.8 dB, out of band rejection of 20 dB, and an FBW of 0.8%.